Ответ:
Пошаговое объяснение:
(32 - m). 6 - 39 = 45
32*6-6m -39=45
-6m = 45+39-192
-6m=-108
m = -108/-6
m = 18
15 768: t = 32 112: 892
15768/ t = 36
t = 15768/36
t=438
192-6m-39=45
192-84-6m=06m=108
m=18
15768:t=36
t=15768:36
t=
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
(32 - m). 6 - 39 = 45
32*6-6m -39=45
-6m = 45+39-192
-6m=-108
m = -108/-6
m = 18
15 768: t = 32 112: 892
15768/ t = 36
t = 15768/36
t=438
Ответ:
192-6m-39=45
192-84-6m=06m=108
m=18
15768:t=36
t=15768:36
t=